EFEKTIVITAS PENGGUNAAN APLIKASI KAHOOT PADA MATA PELAJARAN AQIDAH AKHLAK UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI MA DARUL FIQRI SARIROGO - Salisatuz Zuhro; Ainun Nadlif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the effectiveness of using the Kahoot application in improving student learning outcomes in the Aqidah Akhlak subject at MA Darul Fiqri Sarirogo. The research employed a quantitative approach with a quasi-experimental non-equivalent control group design, involving two classes: an experimental group of 30 students who learned with Kahoot and a control group of 10 students who continued with conventional methods. Data were collected through pre-tests and post-tests to measure cognitive achievement. The findings revealed a significant improvement in the experimental group, with an average score of 8.950, where most students were categorized as Very Good. Meanwhile, the control group only achieved an average score of 8.350 with less consistent outcomes. Beyond cognitive gains, Kahoot also enhanced motivation, active participation, and created a more competitive and engaging classroom atmosphere. These results align with constructivist theory, which emphasizes active learner involvement. Thus, Kahoot is proven to be an effective and innovative medium, well-suited to the digital generation, for improving both the quality and outcomes of Aqidah Akhlak learning.